GW24-e1751 The Diagnosis of Vascular Injury by Ultrasonography Combining Angiography in the Comprehensive Surgical Treatment Shelter. (1st October 2013) - Shibei, Li; yaling, Han
Abstract : Objectives: There is no report about diagnosis of vascular injury by ultrasonography combining angiography in the comprehensive surgical treatment shelter recently. Methods: Producing different site of vascular injury animal models in the comprehensive surgical treatment shelter, using ultrasonography combining angiography to diagnose the vascular injury 0/10/30 min after model created successfully, recording the character of the imaging and comparing there detection rate. Results: 10 vascular injury animal models were created successfully. 2/5/7 hematomas were checked out by ultrasonography, and 10/8/6 bleeding vascular injury were detected by angiography at the 0/10/30 min point. The imaging has different character at the different time point. Conclusions: It was effectiveness for diagnosis of vascular injury by ultrasonography combining angiography in the comprehensive surgical treatment shelter in disaster site or battlefield first-line.